2022
DOI: 10.1364/oe.448714
|View full text |Cite
|
Sign up to set email alerts
|

Flexible composite film with artificial opal photonic crystals for efficient all-day passive radiative cooling

Abstract: All-day passive radiative cooling has recently attracted broader attention for its potential as a viable energy technology. Although tremendous progress has been achieved, the design and fabrication of low-cost high-efficiency radiators for all-day passive radiative cooling remains a challenge. Herein, we report a new type of flexible composite radiator film with built-in artificial opal-like structures for all-day passive radiative cooling. Using artificial opal structure concepts, the proposed polydimethylsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Recently, Nan et al reported a polydimethylsiloxane (PDMS) radiator film with embedded polystyrene (PS) microsphere photonic crystals (Figure 6e). [103] By manipulating the diameter of the microspheres, the opal-like structure achieves low absorptance of solar energy. The inner PS microsphere arrays stimulate optical resonance in sphere-tosphere, sphere-to-layer, and layer-to-layer (Figure 6f).…”
Section: Ordered Array Structurementioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Nan et al reported a polydimethylsiloxane (PDMS) radiator film with embedded polystyrene (PS) microsphere photonic crystals (Figure 6e). [103] By manipulating the diameter of the microspheres, the opal-like structure achieves low absorptance of solar energy. The inner PS microsphere arrays stimulate optical resonance in sphere-tosphere, sphere-to-layer, and layer-to-layer (Figure 6f).…”
Section: Ordered Array Structurementioning
confidence: 99%
“…We compare a variety of typical designs that possess sufficient daytime radiative cooling capabilities (Table 1). [12,15,16,[20][21][22]77,[91][92][93][94][95][97][98][99][101][102][103][104]108,[111][112][113] As evidenced by empirical evidence, these cooling apparatuses exhibit unprecedented cooling efficiency, with a magnitude of 61 to 163.9 W m −2 and an attendant decrease in temperature ranging from 1.88 °C to 13.8 °C. It is noteworthy that the superlative performance of radiative cooling is commonly contingent upon a manifold of photon mechanisms that coalesce to bring about an efficacious outcome.…”
Section: Bioinspired Photonic Structurementioning
confidence: 99%
See 2 more Smart Citations
“…18,19 Among these, photonic structures exhibit tailored spectrum via tuning the subwavelength structural features, realizing distinctive radiative cooling performance. 20,21 Strategies for constructing photonic structures like multilayer stacks, 22 periodic structures, 23 random structures, 24 and bioinspired structures 25 thrive in achieving highly efficient passive radiative cooler. 26 Raman et al 27 first reported a multilayer photonic structure used for radiative cooling with a solar reflectance of 97% and selective emissivity across the atmospheric transparency window.…”
Section: ■ Introductionmentioning
confidence: 99%